2019
DOI: 10.1002/cbdv.201900369
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Cellulase−Ultrasonic Synergistic Extraction Conditions of Polysaccharides from Lenzites betulina

Abstract: Lenzites betulina has been recognized as a rich source of chemical components, including polysaccharides, sterides and sugar alcohols. In this study, cellulase−ultrasonic synergistic extraction method was applied to extract polysaccharides from L. betulina, and the response surface methodology was used to optimize the extraction conditions. The eight basic factors affecting extraction yield were evaluated by Plackett−Burman design (PBD). Then, the four important factors significantly affecting the yield of pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…The conditions that balanced VAP yield and its antioxidant capacity were enzyme loading 2 %, incubation temperature 47 °C, pH 4.1, solid/liquid ratio 1 : 7.6, 2.5 h digestion time, and 2.5 h extraction time. The conditions showed significant difference from some literature, [11,18] which could come from the differences in the target species and the enzyme used.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…The conditions that balanced VAP yield and its antioxidant capacity were enzyme loading 2 %, incubation temperature 47 °C, pH 4.1, solid/liquid ratio 1 : 7.6, 2.5 h digestion time, and 2.5 h extraction time. The conditions showed significant difference from some literature, [11,18] which could come from the differences in the target species and the enzyme used.…”
Section: Discussionmentioning
confidence: 79%
“…It is well‐known that pH has profound effects on enzymatic activities. Too high or too low pHs are all detrimental [18] . Figure 1 (B) indicated that the optimal pH was around 4.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, dried sample was crushed and then decolorized using 10-fold volume of ethanol (80%) at 60 ℃ for 30 min twice by ultrasonic cleaner (SB25-12DTDS, Ningbo Xinyi Ultrasonic equipment co., Ltd), and the organic layer was removed by suction filtration. The residue was extracted under the conditions of cellulase dosage of 0.8%, enzymolysis temperature of 60 °C, enzymolysis time of 180 min, pH of 4.5, liquid–solid ratio of 45 ml/g, ultrasound power of 300 W, ultrasound time of 20 min and ultrasound temperature of 45 °C, respectively [ 32 ]. Secondly, the supernatant were concentrated and then precipitated with a four-fold volume of anhydrous ethanol at 4 ℃ overnight.…”
Section: Methodsmentioning
confidence: 99%
“…Firstly, dried sample was crushed and then decolorized using ten-fold volume of ethanol (80 %) at 60 ℃ for 30 min twice by ultrasonic cleaner (SB25-12DTDS, Ningbo Xinyi Ultrasonic equipment co., Ltd), and the organic layer was removed by suction filtration. The residue was extracted under the conditions of cellulase dosage of 0.8 %, enzymolysis temperature of 60°C, enzymolysis time of 180 min, pH of 4.5, liquid-solid ratio of 45 ml/g, ultrasound power of 300 W, ultrasound time of 20 min and ultrasound temperature of 45°C, respectively [28]. Secondly, the supernatant were concentrated and then precipitated with a four-fold volume of anhydrous ethanol at 4 ℃ overnight.…”
Section: Extraction Of Crude Lbpsmentioning
confidence: 99%